The last interglacial to glacial transition, Togiak Bay, Southwestern Alaska - Kaufman, D. S.; Manley, W. F.; Wolfe, A. P.; Hu, F. S.; Preece, S. J.; Westgate, J. A.; Forman, S. L. (Quaternary Research, 2001)
An 18-m-high coastal bluff at Togiak Bay (northwestern Bristol Bay, southwestern Alaska) exposes marine, lacustrine, fluvial, glacial, volcanic, and organic deposits that record the ∼50,000-year-long transition from the peak of the last interglaciation to the early Wisconsin glaciation. The base of the section is dominated by stratified sand and silt extending up to 4.3 m above sea level; marine diatoms are present, and pollen assemblages are characterized by relatively high percentages of Picea, Alnus, and Betula and low percentages of Poaceae and Cyperaceae. The marine sediment was probably deposited during the peak of marine oxygen-isotope stage (OIS) 5e. An infrared stimulated luminescence (IRSL) age of 151,000±13,000 yr from near the base of the exposure is permissive of this correlation. The marine sand and silt are overlain by 0.8 m of peaty silt with diatoms that record a transition from marine to lacustrine conditions. During this interval, Poaceae and Cyperaceae dominate the pollen assemblages, and Picea and shrubs are nearly absent, suggesting that herb tundra occupied the landscape. This interval probably encompasses OIS 5d on the basis of the herb tundra and an IRSL age of 119,000±10,000 yr from 60 cm below the marine/lacustrine transition. The organic mud is overlain by 3.1 m of stratified sand and organic silt that apparently record shallowing of the lake; reappearance of spruce and shrubs (=OIS 5c?); and subsequent deepening of the lake (=OIS 5b?); followed by aggradation of a floodplain (=OIS 5a?), which was dry at the time basaltic lava buried the site. Thermoluminescence analyses on lava-baked sediment indicate that the eruption occurred 70,000±10,000 yr ago. Sometime thereafter, but prior to 53,600 14C yr B.P. an outlet of the Ahklun Mountains ice cap advanced over the site and deposited ∼7 m of bouldery ice-contact drift. The sedimentary sequence contains at least four tephra beds. Major- and trace-element chemistry provide a basis for correlating two of the tephras with tephra beds at nearby sites. The tephras, luminescence ages, and correlations with marine isotope stages provide the geochronological control to place the Togiak Bay section into a global context. The site serves as an important new reference section for late Pleistocene paleoenvironmental change in eastern Beringia.
id: 1392